LOW-STAKES ASSESSMENT WITHOUT EFFECTIVE FEEDBACK IS WORTHLESS: A DESCRIPTIVE-ANALYTICAL STUDY OF PROGRAMMATIC ASSESSMENT IN UNDERGRADUATE DENTAL EDUCATION - Sundawan, Kertamaya (Journal of Health and Dental Sciences, 2025)
Assessment plays a vital role in the education process. Assessment plays a significant role in the learning process in medical education, serving not only to evaluate learning outcomes but also to declare someone competent. Formative assessment is typically low-stakes, designed to stimulate learning. This low-risk assessment is effective when it is integrated into the ongoing teaching and learning program to facilitate timely, specific, and actionable feedback for students. The aim is to evaluate the effectiveness and sustainability factors of programmatic assessment based on the results of data analysis. The research method used is a descriptive analytical study. This study employed a descriptive-analytical design using a survey of undergraduate student grade data in the Periodontology study program, Faculty of Dentistry, Jenderal Ahmad Yani University. Inclusion criteria were students with longitudinal low-stakes grades, while those not participating in the low-stakes learning process were excluded. Data were analyzed using statistical methods to calculate mean and standard deviation, with institutional approval ensuring confidentiality. The results show that the average low-risk score is 83.94, while the high-risk score has an average of 68.47, with a passing percentage of 100% on low-risk scores, resulting in a very good predicate, and only 7% on high-risk assessments. It suggests that there is no holistic approach to programmatic assessment, which is influenced by several factors, including students not receiving timely feedback, poorly designed final exam questions, and internal factors such as nervousness during the final exam. The conclusion is that programmatic assessment should combine low-stakes and high-stakes assessments. Effective low-stakes assessments can enhance students' preparation for high-stakes exams. Low-stakes assessments can also increase students' motivation to study more deeply and regularly, but this depends on the quality of the feedback provided. DOI : 10.54052/jhds.v5n2.p187-198